Generative Learning Model Refun Box Help On The Mathematic Connection Ability Of Junior High School - Husna, Nurul; Prihatiningtyas, Nindy Citroresmi; Warvani, Uray Desty (STKIP Singkawang, 2025)
Mathematical connection skills are crucial because they are one of the goals of mathematics learning in secondary schools. Students who can connect mathematical concepts mathematically will have a deeper understanding and be able to retain them for longer. This study aims to determine the effect of generative learning models assisted by the refun box props on students' mathematical connection abilities, to find out the motivation and learning response of students using learning with generative models assisted by the refun box props on the relations and functions of class VIII of SMP Negeri 4 Singkawang. This study uses a Quasi-Experimental design. The population in this study were 8th grade students of SMP Negeri 4 Singkawang which consisted of eight classes totaling 253 students. Samples were taken by purposive sampling technique. The sample in this study consisted of two classes, namely VIIIH grade students as an experimental class (using the Generative learning model assisted by the Refund Box teaching aid) and VIIIF grade students as a control class (using direct learning models). The analysis shows: 1) there are differences in students' mathematical connection ability between classes using generative learning models assisted by refun box teaching aids and classes using direct learning models; 2) the effect of generative learning models assisted by refun box props on students' mathematical connection ability is high; 3) student learning motivation is categorized high; 4) student learning responses are categorized as good.Model Pembelajaran Generatif Berbantuan Alat Peraga Kotak Refun Terhadap Kemampuan Koneksi Matematis Siswa SMPN 4 SingkawangABSTRAKKemampuan koneksi matematis merupakan satu diantara kemampuan yang sangat penting karena kemampuan koneksi matematis merupakan salah satu tujuan dari pembelajaran matematika ditingkat sekolah menengah. Siswa yang dapat menghubungkan konsep-konsep matematika secara matematis, siswa tersebut akan memiliki pemahaman yang lebih mendalam dan dapat bertahan lebih lama. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran pembelajaran generatif berbantuan alat peraga kotak refun terhadap kemampuan koneksi matematis siswa, motivasi dan respon belajar siswa saat pembelajaran dengan model generatif berbantuan alat peraga kotak refun pada materi relasi dan fungsi kelas VIII SMP Negeri 4 Singkawang. Penelitian ini menggunakan desain Quasi Eksperimental. Populasi dalam penelitian ini adalah semua kelas VIII SMP Negeri 4 Singkawang yang terdiri dari delapan kelas yang berjumlah 253 siswa. Sampel diambil dengan teknik purposive sampling. Adapun sampel yang dipilih terdiri dari dua kelas yaitu kelas VIIIH sebagai kelas eksperimen dan kelas VIIIF sebagai kelas kontrol. Hasil analisis menunjukkan: 1) adanya perbedaan kemampuan koneksi matematis siswa antara kelas yang menggunakan model pembelajaran generatif berbantuan alat peraga kotak refun dengan kelas yang menggunakan model pembelajaran langsung; 2) pengaruh model pembelajaran generatif berbantuan alat peraga kotak refun terhadap kemampuan koneksi matematis siswa tergolong tinggi; 3) motivasi belajar siswa dikategorikan tinggi; 4) respon belajar siswa dikategorikan baik.Kata Kunci :Model Pembelajaran Generatif; Media Kotak Refun; Koneksi Matematis; Motivasi Belajar; Respon Belajar.